Three‐dimensional mapping of the arteriovenous loop model using two‐dimensional histological methods. Issue 10 (13th July 2016) - Seuss, Hannes; Arkudas, Andreas; Hammon, Matthias; Bleiziffer, Oliver; Uder, Michael; Horch, Raymund E.; Yuan, Quan
Abstract: Objectives: The aim of this study was to create an analytical tool for the three‐dimensional distribution of immunohistochemically stained cells in the arteriovenous (AV) loop model of the femoral vessels of rats that fuses two‐dimensional histological slides into stacks.Methods: A total of 22 AV loops were implanted into male syngeneic Lewis rats by creating an arteriovenous fistula between the femoral artery and vein by interposing a femoral vein graft of the contralateral extremity. This fistula was embedded into an isolation chamber filled with a fibrin matrix. Specimens were explanted after 7 to 14 days, and the AV loop was processed using standard histological protocols. Immunohistochemical staining for HIF‐1α and a counter staining with hematoxylin was performed. Various layouts with different cutting planes, regions of interest, and post‐processing algorithms were evaluated.Results and observations: The proximal‐to‐distal cutting perpendicular to the vascular axis proved to be the best layout for mapping the three‐dimensional constructs containing the AV loop. A semi‐automatic algorithm for the differentiation of immunohistochemical positive and negative cells was developed.Conclusion: The newly established methods from this study constitute an excellent tool for the general evaluation of the AV loop model – particularly with regard to the three‐dimensional distribution of immunohistochemical positive and negative cells.